Development of Kebaya Pattern E-Module Elements Preparation Fashion in Vocational High Schools - Diana Fatonah; Desy Tri Inayah; Enggar Kartikasari (Universitas Negeri Semarang, 2026)
The development of science and technology affects the use of technology in the world of education increasing. This study aims to 1) analyze the e-module of the kebaya pattern on the preparation element of making clothes in Vocational High School, 2) test the feasibility of developing the e-module of the kebaya pattern in the preparation element of making clothes in Vocational High School, 3) find out the response of students to the development of e-module for making new kebaya patterns in the preparation element of making clothes in Vocational High School. This type of research is research and development using the four-D development model, namely define, design, development, and dissemination. Data collection uses observation, documentation, and questionnaires. Development of a Kutu Baru Kebaya pattern e-module through a flipbook heyzine. The results of the study showed that: 1) the Kutu Baru Kebaya pattern e-module on the preparation element for making flipbook clothing equipped with pictures and videos of making new kutu kebaya patterns can be accessed anytime and anywhere, 2) the e-module developed is suitable for use based on material experts with a percentage of 100% (feasible) and media experts with a percentage of 100% (feasible), and 3) students' responses to the Kutu Baru Kebaya pattern e-module in small-scale trials got a percentage of 88.03% (strongly agree) and the limited-scale trial got a percentage of 88.10% (strongly agree).